Pengaruh Pengetahuan, Sikap Ibu dalam Pemberian Taburia pada Balita Stunting Terhadap Berat Badan di Posyandu RW VIII Puskesmas Bulak Banteng Surabaya - Sri Anik Rustini; Muh Zul Azhri Rustam (Sekolah Tinggi Ilmu Kesehatan Hang Tuah Surabaya, 2020)
The Taburia program is an effort to increase body weight in stunting toddlers. Some mothers do not know about the provision of taburia for stunting toddlers. The problem of stunting growth in toddlers is still common, especially in coastal communities, mothers do not understand how to meet the nutritional needs of children under five. The purpose of this study was to determine the knowledge, attitudes of mothers in giving taburia to stunting toddlers on body weight at posyandu. The research design used the One Group Pre-post Test Design on giving taburia and the Cross-Sectional Study to measure the knowledge and attitudes of mothers. The sample of the study was 150 mothers with stunting toddlers. The sample technique used simple random sampling. The independent variable of this study is knowledge, the mother's attitude is measured by a structured questionnaire. The dependent variable is measuring body weight using a weight scale. Data were analyzed by using Chi-Square test. The results of this study indicate that there is an effect on changes in body weight in giving taburia for two weeks for 2 months, and there is an influence between mother's knowledge and there is no effect of mother's attitude on body weight in giving taburia to stunting toddlers. The fulfillment of taburia nutrition in stunting toddlers can be optimal if the family is active in looking for the latest information about the provision of taburia and posyandu cadres often conduct socialization on giving taburia to stunting children.Keywords: Taburia, Mother's Knowledge, Mother's Attitude, Body Weight, Stunting